Determinants of Public Organization Performance with Accountability and Organizational Commitment as Moderator at BPN Buleleng Regency - Luh, Resiani; Sujana, Edy; Diatmika, Putu Gede (Universitas Pendidikan Ganesha, 2022)
This research aimed to determine: (1) the effect of internal control on the performance of public organizations, (2) the effect of the quality of information systems on the performance of public organizations, (3) accountability can moderate the effect of internal control on the performance of public organizations, (4) organizational commitment can moderate the effect of internal control on the performance of public organizations, (5) accountability can moderate the effect of the quality of information systems on the performance of public organizations, and (6) organizational commitment can moderate the effect of the quality of information systems on the performance of public organizations. The research design used was causal quantitative using primary data obtained from questionnaires. The population of this study were all 132 employees of BPN Buleleng Regency. The sampling technique in this study used a saturated sample with a total of 132 respondents. The data analysis technique used SEM PLS. The results show that (1) internal control had a positive effect on the performance of public sector organizations, (2) the quality of information systems had a positive effect on the performance of public sector organizations, (3) accountability can moderate the influence of internal control on the performance of public organizations, (4) organizational commitment can moderate the effect of internal control on the performance of public organizations, (5) accountability can moderate the effect of the quality of information systems on the performance of public organizations, and (6) organizational commitment can moderate the effect of the quality of information systems on the performance of public organizations.